Differently localized lysophosphatidic acid acyltransferases crucial for triacylglycerol biosynthesis in the oleaginous alga Nannochloropsis. (28th March 2017) - Nobusawa, Takashi; Hori, Koichi; Mori, Hiroshi; Kurokawa, Ken; Ohta, Hiroyuki
Summary: The production of renewable bioenergy will be necessary to meet rising global fossil fuel demands. Members of the marine microalgae genus Nannochloropsis produce large quantities of oils (triacylglycerols; TAGs), and this genus is regarded as one of the most promising for biodiesel production. Recent genome sequencing and transcriptomic studies on Nannochloropsis have provided a foundation for understanding its oleaginous trait, but the mechanism underlying oil accumulation remains to be clarified. Here we report Nannochloropsis knock‐out strains of four extraplastidic lysophosphatidic acid acyltransferases (LPAT1–LPAT4) that catalyze a major de novo biosynthetic step of TAGs and membrane lipids. We found that the four LPATs are differently involved in lipid metabolic flow in Nannochloropsis . Double knock‐outs among the LPATs revealed the pivotal LPATs for TAG biosynthesis, and localization analysis indicated that the stramenopile‐specific LPATs (LPAT3 and LPAT4) associated with TAG synthesis reside at the perimeter of lipid droplets. No homologous region has been found with other lipid droplet‐associated proteins, however. Lipid droplets are an organelle found in nearly all organisms, and recently they were shown to play important roles in cellular metabolism and signaling. Our results provide direct evidence for the importance of the perimeter of lipid droplet in TAG synthesis in addition to its known role in maintaining TAG stability, and these findings suggest that the oleaginous trait of Nannochloropsis is enabled by the acquisition of LPATs at the perimeter of lipid droplets. Significance Statement: We have identified the main enzymes, called lysophosphatidic acid acyltransferases, of oleaginous alga Nannochloropsis that are central players for production of utilizable triacylglycerols. Intriguingly, two of these acyltransferases are located at the perimeter of lipid droplets, which are found in nearly all organisms, and these droplets have recently been shown to play important roles in cellular metabolism and signaling.